The Domination of Ideas and Intellectuality in Gaining the Power and Hegemony in the Play Man and Superman by George Bernard Shaw - Wajiran Wajiran (Humaniora, 2013)
This study aims to reveal the concept of hegemony of a drama entitled Man and Superman. The play is written by a social and political activist in which contains important lessons for social change. For that reason, the drama is regarded as a propaganda led by the author for making changes in the society. This study uses sociological theory, especially Antonio Gramsci's theory,  Hegemony. By using this theory, it is expected that the relationship between the literature and the condition of the society at that time that triggers the birth of this work as well as the author’s hopes and expectation would be understood. Through this approach, it is expected that the norms and educational values embodied in the drama would be revealed and understood.